PENGARUH TINGKAT PENDIDKAN, PENGANGGURAN PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN DI D.I.YOGYAKARTA PRIODE 2010-2017 - Suripto, Suripto; Subayil, Lalu (LPPM Universitas Muhammadiyah Mamuju, 2020)
This study uses secondary data with panel data analysis tools, which consist of time series data during the period 2010-2017 and cross section data 5 Districts / cities in the Special Province of Yogyakarta. The analysis model used in this study to estimate the panel data regression model is to use the fixed effect model.The results in the study with a significance level of 5% indicate that (1) education level variables have a negative and not significant effect on poverty; (2) negative unemployment variables and no significance for poverty; (3) the variable rate of economic growth has a negative and significant effect on poverty; (4) the human development index variable has a negative and significant effect on poverty.